Study of evaluation of Alvarado scoring system in acute appendicitis - Puttaraju, Shashidhara; D. Y., Deva Keerthana (International Surgery Journal, 2019)
Background: Acute appendicitis is one of the most common surgically correctable acute abdomen presenting at emergency department worldwide. Inspite of all advances in diagnostic modalities and surgical techniques, diagnosis remains difficult sometimes as a challenge and delayed decision making complicates this surgical disease. Alvarado scoring system is one of available scoring system for diagnosis of acute appendicitis, based on history, clinical examination, lab investigations and easy to apply, helps in clinical decision regarding planning surgery and avoid negative laparotomies. The aim of the study was to evaluate diagnostic accuracy of Alvarado scoring system in preoperative diagnosis of acute appendicitis and correlating with postoperative findings. Methods: This study was conducted in 100 cases of suspected appendicitis admitted in surgery department of Rajiv Gandhi Speciality Hospital, Agatti Island, Lakshadweep, Union territory of India, from July 2015 to June 2017 adopting Alvarado scoring system. Results were analyzed. Results: Out of 100 patients admitted with suspected acute appendicitis, number of cases operated suspecting acute appendicitis were 83 of which 80 were found to have acutely inflamed appendix. Results of Alvarado score of operated patients are as follows: 80 patients had score 7-10, and 3 patients had score 5-6, patients with Alvarado score <5 (17 pts) were managed conservatively. Conclusions: The Alvarado scoring system is a simple and useful diagnostic tool for diagnosis of acute appendicitis with acceptable sensitivity and specificity and can be used with high degree of accuracy. Our findings suggest that patients presenting with abdominal pain and Alvarado scores greater than 7 are more likely to have appendicitis.